(untitled) (New York, 2006)
Written by an interdisciplinary team, Low Back Syndromes is the first truly comprehensive multidisciplinary text for low back conditions. Because today’s patients expect their clinicians to possess an in-depth understanding of available treatments, this text covers the broad spectrum of clinical options currently available. From chiropractic to osteopathy, from medicine to physical therapy, from occupational medicine to evidence based health care, from psychology to surgery, from pain medicine to manipulation, from post-surgical rehabilitation to end-stage training of elite athletes, this is the first textbook to bring all the specialists together to allow clinicians direct access to state-of –the art standards of practice from a single source. Featuring internationally acclaimed contributors from a variety of specialties, this text is a practical guide for mastery of both traditional and newer techniques.
Keywords: Backache,Đau lưng; Treatment,Điều trị